2004
DOI: 10.1038/ni1030
|View full text |Cite|
|
Sign up to set email alerts
|

The costimulation-regulated duration of PKB activation controls T cell longevity

Abstract: A brief antigenic stimulus can promote T cell proliferation, but the duration and nature of intracellular signals required for survival are unclear. Here we show that in the absence of OX40 costimulation, antigen-activated CD4+ cells are short-lived because the activity of protein kinase B (PKB; also known as Akt) is not maintained over time. Activated T cells that express a dominant-negative variant of PKB also undergo apoptosis, reproducing the OX40-deficient phenotype. In contrast, an active form of PKB pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
184
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(196 citation statements)
references
References 49 publications
10
184
1
1
Order By: Relevance
“…TRAFs mediate OX40 signals via NF-κB-inducing kinase (NIK) that activate noncanical NF-κB activation, a PI3K-independent pathway (31). In addition, several groups reported that OX40 signals could sustain PI3K/PKB activities, which may also impact on canonical NF-κB activation (15,16). More importantly, recent data directly showed that OX40 signaling could target the NF-κΒ1 pathway in peripheral antigen-responding CD4 T cells.…”
Section: Common Pi3k/pkb/nf-κβ Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…TRAFs mediate OX40 signals via NF-κB-inducing kinase (NIK) that activate noncanical NF-κB activation, a PI3K-independent pathway (31). In addition, several groups reported that OX40 signals could sustain PI3K/PKB activities, which may also impact on canonical NF-κB activation (15,16). More importantly, recent data directly showed that OX40 signaling could target the NF-κΒ1 pathway in peripheral antigen-responding CD4 T cells.…”
Section: Common Pi3k/pkb/nf-κβ Pathwaysmentioning
confidence: 99%
“…However, the mechanism of how costimulation regulates T cell proliferation is still unclear. The enhanced proliferation mediated by costimulation is strongly correlated with the increased cytokine secretion, i.e., IL-2 and IL-12, which promote T cell proliferation (12,15,58).…”
Section: Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…OX40 -/-T cells have a defect in long term survival. This survival defect is rescued by retrovirus mediated overexpression of Bcl-2, Bcl-x L or activated Akt kinase [232,233]. OX40L is detected on activated B cells, macrophages and dentritic cells [234].…”
Section: Costimulatory Molecules and Anti-apoptotic Molecules In T Cellsmentioning
confidence: 99%